(untitled) (Historia, 2021)
Defending the Cape in 1795: for king or country? The strategic location of the Cape of Good Hope on the southern tip of Africa made it a priced possession and vital for maritime communications to the East. With the growth of British global commercial interest control of the sea route to the East and a safe base along this route became essential. But, the Cape was in Dutch hands and in 1795 (after France invaded the Netherlands) Britain decided to prevent the Cape from falling into French hands. An expeditionary force sailed for the Cape and the Prince of Orange (then a refugee at Kew) supported the idea that the Cape be placed "under the protection" of the British. Local opinion at the Cape was severely divided. Some Orange supporters demanded immediate adherence to the Prince of Orange's request while supporters of the Patriot Party threatened to defend the Cape to the last. As the rulers of the Cape and many officers were Orange supporters and the burghers and soldiers were Patriot supporters, the Cape Military Commander Colonel Gordon, was in a difficult position. Should he defend the Cape or capitulate? Meanwhile, the British landed successfully in False Bay and because of the poor defence they forced the Dutch back. Many of the burghers and soldiers were furious with the weak defence, but when British reinforcements arrived, the military situation changed in favour of the British. the Cape capitulated.